Effectiveness of Peanut Shell Activated Carbon as an Adsorbent for Co(II) and Cu(II) Metals in Waste Water Using a Continuous System - Hanifah, Rizka Aulia; Kristianingrum, Susila (Indonesian Journal of Chemistry and Environment, 2025)
This study aims to investigate the characteristics and performance of physic-chemically activated peanut shell adsorbent in reducing Co(II) and Cu(II) metal concentrations from textile industry wastewater. The activation process involved heating at 450°C and immersion in 0.5 M NaOH. Adsorbent characterization was conducted according to SNI 06-3730-1995 and analyzed using SEM-EDX. Adsorption was carried out in a continuous column system with variations in flow rate, adsorbent mass, and initial concentrations of Co(II) and Cu(II). The unactivated adsorbent had a moisture content of 3.11%, ash content of 5.54%, volatile matter of 64.01%, carbon content of 85.43%, and iodine adsorption of 261.68 mg/g. After activation, these values changed to 3.99%, 7.45%, 53.88%, 74.50%, and 355.32 mg/g, respectively. Optimum adsorption of Co(II) occurred at a flow rate of 0.0358 mL/s and 0.9 g adsorbent mass, while for Cu(II), the optimum was at 0.1282 mL/s and 0.9 g. The optimal volume ratio for both metals was 1:2 (v/v). Adsorption efficiency reached 78.34% for Co(II) and 99.98% for Cu(II), with adsorption capacities of 7.95 mg/g and 9.73 mg/g, respectively.